Optimal risk allocation in rural next generation infrastructure projects and the role of adequate network modeling: Next generation access, broadband infrastructure projects, business case model - Stephan Wirsing (International Telecommunications Society (ITS), 2012)
Throughout the last decade, the telecommunications sector has been subject to substantial changes in most countries of the world. Increased computational power, higher transmission capacities in combination with an openly and independently designed transport layer for packet switched data (IP) allow for a vast degree of freedom regarding the architecture and independence of services. Especially the transition towards All-IP networks in both, the mobile and the fixed sector, is expected to further extend the scope for end user applications. The usability of the IP-protocol for multiple types of services enables their provision via the same network, and thus services become more independent from physical network infrastructure. Networks with these features are commonly referred to as Next Generation Networks (NGN) or Next Generation Access networks (NGA), respectively. In consequence, operators are confronted with the challenge to fulfill a large number of technological requirements that emerge from the huge variety of distinct service characteristics.
Keywords: 330